User Satisfaction Analysis on the Strava Application in Palembang City using the Usability Method - Muhammad Hafiz Al Zaky; Apriansyah Putra; Ari Wedhasmara; Ken Ditha Tania (SISTEMASI, 2026)
This study aims to evaluate user satisfaction with the Strava application in Palembang through a usability approach. A quantitative research design was employed involving 100 Strava users as respondents. The study examined Learnability, Efficiency, Memorability, and Errors as usability dimensions influencing User Satisfaction. Data were collected through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The results indicate that all measurement indicators satisfied the required validity and reliability criteria. Hypothesis testing revealed that, individually, only the Errors dimension had a significant effect on user satisfaction, whereas Learnability, Efficiency, and Memorability did not show significant effects. However, when considered simultaneously, all usability dimensions collectively contributed to user satisfaction. These findings suggest that system stability and a low error rate are the primary factors influencing user satisfaction with the Strava application.